Child maltreatment and substance use: a behavior genetic analysis - Azimi, Andia M. (Child maltreatment, 2022)
Child maltreatment is a pervasive social problem often perpetuated by family members and is related to a wide array of negative life outcomes. Although substance use is an outcome commonly associated with experiences of child maltreatment, not all individuals who experience maltreatment struggle with such issues. Many individuals can positively adapt to experiences of maltreatment based on levels of resilience and susceptibility. Research suggests that genetic differences may partly explain why negative outcomes develop for some, but not for others. Few studies have examined the extent to which genetic and environmental factors influence the longitudinal association between child maltreatment and varying forms of substance use, leaving a fundamental gap in our current understanding of this association. The current study aims to address this gap by analyzing a sample of twins from the National Longitudinal Study of Adolescent to Adult Health (Add Health). Findings from a series of univariate and bivariate biometric models reveal that the longitudinal associations between maltreatment, cigarette use, and marijuana use are accounted for by additive genetic and nonshared environmental factors. Moreover, the magnitude of the contribution varies across unique subgroups of cigarette and marijuana use. Directions for future research and theoretical implications are discussed.